Conjoint analysis on Mongolian meat consumption (Mongolian Journal of Agricultural Sciences, 2014)
The diet in Mongolia is essentially based on animal products: meat, considered as "red food", and dairy products, "white food". Related to urbanization and changes of lifestyle, Mongolian food consumption structure is changing. But, meat is still important food for Mongolians. Therefore, Improvement of meat quality and meat safety issues is core issues of meat production and meat consumption. The study applied conjoint analysis methodology for consumer choice of meat. In result of Conjoint Analysis, Mongolians prefer good price and high fat content meat and safety meat. In future, the Mongolian Government should be oriented meat production and supply with trade mark and increase a production of Mongolian Brand meat. DOI: http://dx.doi.org/10.5564/mjas.v11i2.234 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.133-137